Monopoly power limits hedging - Alexander Muermann; Stephen H. Shore (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
When a spot market monopolist participates in a derivatives market, she has an incentive to deviate from the spot market monopoly optimum to make her derivatives market position more profitable. When contracts can only be written contingent on the spot price, a risk-averse monopolist chooses to participate in the derivatives market to hedge her risk, and she reduces expected profits by doing so. However, eliminating all risk is impossible. These results are independent of the shape of the demand function, the distribution of demand shocks, the nature of preferences or the set of derivatives contracts.
urn:nbn:de:hebis:30-60646
Keywords: D24; G32; 330; Spot Market Power; Derivates Market; Hedging; Spotmarkt; Monopol; Finanzderivat; Finanzmarkt; Hedging; Theorie